2022
DOI: 10.1080/19420862.2022.2076295
|View full text |Cite
|
Sign up to set email alerts
|

The proximity of the N- and C- termini of bovine knob domains enable engineering of target specificity into polypeptide chains

Abstract: Cysteine-rich knob domains can be isolated from the ultralong heavy-chain complementarity-determining region (CDR) 3, which are unique to a subset of bovine antibodies, to create antibody fragments of ~4 kDa. Advantageously, the N- and C- termini of these small binding domains are in close proximity, and we propose that this may offer a practical route to engineer extrinsic binding specificity into proteins. To test this, we transplanted knob domains into various loops of rat serum albumin, targeting sites tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The ultralong knob domain itself has been isolated from the full IgG framework and shown to be able to bind to antigens of interest with similar affinity to the whole IgG [59,60]. Other studies have engineered knobs into protein loops to produce novel multivalent molecules [61][62][63][64][65]. In addition to binding, a recent study demonstrated that recombinant knob domains alone are able to potently neutralize SARS-CoV-2 [34] .…”
Section: Discussionmentioning
confidence: 99%
“…The ultralong knob domain itself has been isolated from the full IgG framework and shown to be able to bind to antigens of interest with similar affinity to the whole IgG [59,60]. Other studies have engineered knobs into protein loops to produce novel multivalent molecules [61][62][63][64][65]. In addition to binding, a recent study demonstrated that recombinant knob domains alone are able to potently neutralize SARS-CoV-2 [34] .…”
Section: Discussionmentioning
confidence: 99%
“…They have been engineered for use as multivalent molecules, knobbody proteins, and functional knob-only proteins [40][41][42][43][44][45][46]. They have also been engineered to bind and potently neutralize SARS-CoV-2 as recombinant knob domains, highlighting their potential as anti-viral therapeutics [47].…”
Section: Discussionmentioning
confidence: 99%
“…This may enable construction of head-to-tail fusions free from the binding site steric occlusion. Moreover, the proximity of N- and C-termini makes knob domains well suited for grafting onto loops of various proteins, including conventional antibody fragments ( 44 ). Five different formats of bispecific knob domain fusions have been described to date: knob domains transplanted into a framework II loop of a VHH ( 44 ), framework III loop of a Fab fragment ( 45 ), and either AB or EF loops of a full-length IgG CH3 domain ( 46 ), as well as an IgG-like bispecific format described in ( 47 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the proximity of N- and C-termini makes knob domains well suited for grafting onto loops of various proteins, including conventional antibody fragments ( 44 ). Five different formats of bispecific knob domain fusions have been described to date: knob domains transplanted into a framework II loop of a VHH ( 44 ), framework III loop of a Fab fragment ( 45 ), and either AB or EF loops of a full-length IgG CH3 domain ( 46 ), as well as an IgG-like bispecific format described in ( 47 ). However, all these formats combine a knob domain with a larger antibody fragment and therefore do not leverage small size of the former in full.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation